Hubungan Frekuensi Kunjungan Ke Dokter Gigi Dengan Status Kesehatan Gigi Dan Mulut Anak Sekolah Dasar Di Wilayah Kerja Puskesmas Mamajang Kota Makassar - ariani, tri andini; Ilmianti; Nur Rahmah Hasanuddin; Taufan Lauddin; Selviani, Yusrini (YARSI Dental Journal, 2025)
Every year, the fields of medicine and dentistry in Indonesia require more dental skills to provide excellent service and improve the quality of care. Oral health in children often shows suboptimal conditions, with a lot of plaque and other deposits on their teeth. According to the 2023 Indonesian Health Survey (SKI), half of the population over 3 years old complains about dental problems, with South Sulawesi having the second-highest rate at 68.4%. Of the 56.9% of people experiencing dental problems, only 11.2% visit a dentist. Between the ages of 8 and 12, dental changes require more intensive care, with a child’s motivation and support from their environment influencing their oral hygiene. This study aimed to determine the relationship between the frequency of dental visits and the oral health status of elementary school children in the working area of Mamajang Health Center, Makassar City. It was an analytical observational study with a sample of 120 elementary school students in the Mamajang Health Center area. Data were collected through questionnaires and intraoral examinations using the OHI-S index. Of the students, 69.2% had low dental visit frequency, and 31.7% had good oral hygiene status. No significant relationship was found between the frequency of dental visits and oral hygiene status (P-Value > 0.05). The frequency of dental visits does not significantly affect the oral hygiene status of elementary school students.